Assessment of Healthcare Workers’ Perception of Health Hazards and Management’s Safety Practices - Ogbonda, Priscilia Nyekpunwo (British Journal of Healthcare and Medical Research, 2023)
Health workers are vital workforce in the society globally. In many countries, such as Sub-Sahara Africa, workers are at great risk of preventable, life-threatening work-related hazards. The impacts of these hazards are irrefutably crucial generally such as health workers’ shortage, apathy, patient and health workers’ vulnerability to infections, poor services, cost effect, death etc. Hence, this study assesses health worker’s perception of health hazards as well as management safety practices in selected public hospitals in Rivers State, Nigeria. Descriptive cross-sectional design and a sample size of 347 were used. The study employed a multi-staged sampling technique and a structured instrument based on a coefficient of 0.88 as reliability. Descriptive and inferential statistics were used for data analysis. Results revealed good health worker perception of health hazards but poor management’s safety practices. However, management opined that there are protective measures and safety procedures meant to reduce risk of health hazards in the hospitals. Also, there is no significant (p>0.05) association between health workers perception of health hazards and socio-demographic variables. Therefore, to limit frequent health hazards, there is great need for strong advocacy on health hazards, standard safety rules and good management safety practice in the hospitals. It is of importance for the government and hospital managements to develop quality safety management system, integrated standard safety regulation policies and procedures in conformity with global best practices.